2019
DOI: 10.1111/myc.13038
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and risk factors for mortality of invasive non‐Aspergillus mould infections in patients with haematologic diseases: A single‐centre 7‐year cohort study

Abstract: Summary Since mould‐active azole prophylaxis has become a standard approach for patients with high‐risk haematologic diseases, the epidemiology of invasive fungal infections (IFIs) has shifted towards non‐Aspergillus moulds. It was aimed to identify the epidemiology and characteristics of non‐Aspergillus invasive mould infections (NAIMIs). Proven/probable NAIMIs developed in patients with haematologic diseases were reviewed from January 2011 to August 2018 at Catholic Hematology hospital, Seoul, Korea. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 22 publications
0
20
0
3
Order By: Relevance
“…[76,92]. Thus, patients with localized disease and no significant comorbidities would have been operated, while patients with extensive disease would have been managed medically, leading to a selection bias [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[76,92]. Thus, patients with localized disease and no significant comorbidities would have been operated, while patients with extensive disease would have been managed medically, leading to a selection bias [15].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is commonly believed that the survival of mucormycosis, including PM, has improved over time. Some series also suggest excellent results in PM (up to 90% survival at 6 weeks) with combined medicalesurgical therapy [14,15]. The advent of newer mould-active triazoles and better surgical techniques could contribute to better outcomes [16e20].…”
Section: Introductionmentioning
confidence: 99%
“…An Australian study from 2004 to 2012 showed that Mucorales accounted for 45.7% (74/162) of NAMI 13 . Haematological malignancy (48%) has been identified as the most common risk factor 12 . Contrary to European studies, Lichtheimia spp.…”
Section: Question 1 Which Are the Common Nam And What Are The New Risks Identified For Nami?mentioning
confidence: 99%
“…Mucormycosis is the most common NAMI 6,9–12 . An Australian study from 2004 to 2012 showed that Mucorales accounted for 45.7% (74/162) of NAMI 13 .…”
Section: Question 1 Which Are the Common Nam And What Are The New Risks Identified For Nami?mentioning
confidence: 99%
“…Therefore, early and accurate diagnosis of invasive fungal infection (IFI) is important to improve patient survival [3,4]. When neutropenia lasts more than 7 days, fungal infections may occur (aspergillosis, candidiasis, mucormycosis) [5][6][7]. The clinical diagnosis of fungal pulmonary infection is based on host factors (i. e., immune status, neutropenic fever), clinical signs (unexplained fever despite broad-spectrum antibiotics), microbiological evidence of infection, and specific patterns on computed tomography (CT) imaging [1,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%